Matching in-situ and ex-situ recorded stress gradients in an AlxGa1 − xN Heterostructure: Complementary wafer curvature analyses in time and space. (1st April 2018) - Reisinger, M.; Ostermaier, C.; Tomberger, M.; Zechner, J.; Sartory, B.; Ecker, W.; Daumiller, I.; Keckes, J.
Abstract: In-situ wafer curvature measurements and ex-situ ion-beam layer removal method are used to evaluate residual stress depth profiles in a 1.8 μm thick Alx Ga1 − x N heterostructure on Si(111) by evaluating substrate surface curvatures and deflections of stepwise ion-beam milled micro-cantilevers, respectively. Both approaches reveal oscillatory stress depth gradients which correlate excellent in their depth alternations. Differences are found locally in the magnitudes of the stress concentrations, especially in the regions with relatively large stresses, inhomogeneous microstructures and at relatively small thicknesses. The discrepancies are interpreted by local stress relaxations in the growing heterostructure, like dislocation formation and overgrowth by differently stressed regions. Graphical abstract: Image 1